Anxiety and depression levels among multidisciplinary health residents - Daniela Salvagni Rotta; Maria Helena Pinto; Luciano Garcia Lourenção; Priscila Regina Teixeira; Elizangela Gianini Gonsalez; Claudia Eli Gazetta (Rev Rene)
Objective: to assess symptoms of anxiety and depression of professionals of Multidisciplinary Health Residence Programs. Methods: this is a cross-sectional study, performed with fifty professionals, using three instruments: one for socioeconomic and demographic data, and the Beck’s Anxiety and Depression Scale.Results: predominance of females (92.0%), average age 26 years old, single (88.0%), family income from two to five salaries (56.0%) satisfied with the work (82.0%) and thought about quitting the program (56.0%) showed anxiety (50.0%) and depression (28.0%). Conclusion: there was an association between anxiety and depression in multidisciplinary residents, which points to the need for rethinking strategies for identifying these symptoms and control of stress factors for the promotion of mental health.